THE SPIN-OFF EFFECTIVENESS OF SHARIA INSURANCE IN INDONESIA: ANALYZING THE EFFICIENCY AND THE CRITERIA - Erny Arianty; Abdul Ghoni (Universitas Airlangga, 2022)
This research aims to determine the effectiveness of the spin-off implementation in Indonesia by comparing the efficiency of the full-pledge sharia insurance industry with the Sharia Business Unit (SBU) and analyzing the spin-off criteria. The method used is the mixing method. The quantitative method-Data Envelopment Analysis (DEA) in measuring efficiency and descriptive qualitative by conducting interviews with informants from the insurance shariah industry, AASI, OJK, and BKF for spin-off criteria analysis. . The data used is the input data being assets, operating expenses, while the output data is profit and operating income. Efficiency on profit for SBU is higher than full-pledged companies. Efficiency on revenue is slightly different where the efficiency values of full-pledge companies are not entirely at the bottom. Related to spin-off criteria, the SBU industry has not achieved the number of tabarru funds and participant investment of 50% of the parent fund. Based on these facts, the effectiveness of the spin-off implementation has not been realized optimally. This is because the objectives of increasing efficiency and growing the number of industries have not been achieved. The factors that support the realization of effectiveness are leadership commitment, financial management strategies, professional human resources, the role of government and regulatory bodies